P166 Calprotectin in patients with perianal fistula: the CANALS study. (30th January 2023) - Becker drs., M; Stevens, T; de Voogd, F; Wildenberg, M; Gecse, K; Buskens, C
Abstract: Background: Previous studies suggest that faecal calprotectin can be used to discriminate Crohn's disease (CD) perianal fistulas from cryptoglandular (CG) perianal fistulas. The aim of this research was to prospectively validate these findings and further investigate local calprotectin production inside fistula tracts. The aim of the current study was to prospectively analyse the clinical value of calprotectin levels in both the faeces and the fistula tract. Methods: In this prospective study, all consecutive patients with an active perianal fistula undergoing examination under anesthetics were included. Faecal and scraping calprotectin levels collected during surgery were measured. The primary objective was to differentiate between active CD perianal fistulas and CG perianal fistulas based on faecal calprotectin. Secondary outcome parameters were the levels of local calprotectin in fistula tracts and the correlation with fistula characteristics and clinical prognostic parameters like the Geldof Classification system. Results: Sixty-three fistula patients were included in this study (CD n=45; CG n=18). Faecal calprotectin values were significantly higher in CD patients compared to CG patients (396.8 [61.9-1136.8] vs. 47.3 [14.6-233.6] ug/g, p=0.004). The Area Under the Curve (AUC) was 0.733 (95% CI [0.644 to 0.903] with an optimal FC cut-off value of 344ug/g. Faecal calprotectin was not related to calprotectin levels in fistula scrapings which was not significantly different in CD and cryptoglandular fistulas (p=0.893). Calprotectin in fistula scrapings was also not related to fistula characteristics like number of tracts, duration of disease or (previous) seton drainage. However, a significant correlation was found between scraping calprotectin and fistula disease severity and prognosis as defined by a new Geldof classification system: Patients in group 2a (amenable for fistula repair) had significantly lower calprotectin levels (140 [31.0-149.0])ug/g) when compared to class 2b (symptom control) (706 [198.5 – 1936]ug/g, p=0.054) and class 2c (gradually debilitating disease) (3464.0 [328.5-5692.0]ug/g, p=0.008). Patients in class 3 (exhausted perineum) had the highest calprotectin levels highest (5928.0 [2605.0-6000]ug/g). Conclusion: CD and CG perianal fistulas can be distinguished by measuring faecal calprotectin levels. The difference can not be explained by local fistula calprotectin production as calprotectin in fistula scrapings is not predictive of CD. However, the results of this study suggest that scraping calprotectin levels may be used to classify fistula patients and predict outcome of fistula treatment.